Discerning Recurrent Factors in Construction Disputes through Judicial Case Studies—An Indian Perspective - B. Hemanth Sai Kalyan; Anandh Sekar; S. Sindhu Nachiar; P. T. Ravichandran (Buildings, 2022)
Construction disputes have become a recurrent phenomenon in the industry, due to which progress is halted. From a bird’s eye perspective, the most frequent cause of a dispute might be payment issues. However, when observed keenly, it has an inter-relationship with almost every other cause, such as contractual changes, delays in project completion, compromising on the quality of construction, etc. Therefore, analyzing the factors which cause a dispute is important. It is also essential to understand the interrelationship of the factors. In this study, judicial construction disputes, along with judgements in different domains, were collected. The most frequent causes of disputes are identified among these cases. Sixty-five cases were considered for the analysis, which constitutes the writ petition, response and final judgment. These items were collected to gain the perspective of the petitioners and respondents over the cause of the dispute and the final judgment to analyze the factors responsible for decision-making. Factor analysis is done to find out the influencing factors, interrelationships and similarities of the disputes respectively. Among the 8 major factors identified, a strong, positive correlation was found between Poor Performance related issues and Payment related issues. By performing Principal Component Analysis (PCA), causes were classified into 3 domains based on their variables.